Penyuluhan Hak Keterwakilan Perempuan Dalam Pembangunan Hukum Indonesia Kepada Siswi SMKN 44 Jakarta - Liany, Lusy; Jufri, Ely Alawiyah; Umardani, Mohammad Kharis (Jurnal BALIRESO, 2023)
In Law no. 7 of 2017 concerning Elections which are the legal basis for the implementation of the 2019 elections. This provision is contained in Article 245 mandating that the list of prospective candidates must contain at least 30 percent women's representation. In the Indonesian context, legal reform with a justice perspective through the insistence of a 30% quota for women in parliament is a contribution from the liberal feminist experience. The regulation regarding the mandatory 30 percent quota for female candidates is one of the important achievements in Indonesia's post-reform democracy journey. These conditions must be met by political parties in order to participate in the Election. This 30 percent figure is based on the results of UN research which states that a minimum number of 30 percent allows a change to occur and has an impact on the quality of decisions taken in public institutions. However, the issue of gender inequality is clearly reflected in the low representation of women in the structure of Indonesia's representative institutions. Based on the 2010-2035 Indonesian Population Projection data, out of a total of 261.9 million Indonesians in 2017, the female population is 130.3 million or around 49.75 percent of the population. Unfortunately, the large population of women is not represented in parliament. The proportion of women in DPR seats is much less than the proportion of men.